Method for improving wettability of precursor solution and preparing efficient solar cell

By preparing the nanometal oxide layer on the carrier transport layer, the problem of poor perovskite solution in perovskite solar cells is solved, and the high coverage and crystallization quality of the perovskite absorber layer are achieved, which significantly improves the performance and yield of the solar cell.

CN119894334APending Publication Date: 2025-04-25UNIV OF JINAN
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510051518.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In perovskite solar cells, the perovskite solution cannot be fully infiltrated due to the hydrophobicity of the carrier transport layer, resulting in poor density and flatness of the perovskite film, and many holes exist, which affects the performance and yield of solar devices.

Method used

A wet coating process is used to prepare a nanometal oxide layer on the carrier transport layer to improve the wettability of the perovskite precursor solution, thereby improving the coverage and crystallization quality of the perovskite absorber layer.

Benefits of technology

By improving the wettability of the perovskite precursor solution, the coverage and crystallization quality of the perovskite absorber layer are significantly improved, the non-radiative recombination of the interface is reduced, and the yield rate and photoelectric conversion efficiency of solar cells are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119894334A_ABST
    Figure CN119894334A_ABST
Patent Text Reader

Abstract

The invention relates to a perovskite solar cell preparation technology, and particularly discloses a method for improving wettability of a precursor solution and preparing a high-efficiency solar cell. By preparing the metal oxide layer on the hole transport layer, the wettability of the perovskite precursor is improved, the coverage rate of the perovskite light absorption layer is further improved, the electron transport layer, the buffer layer, the passivation layer and the metal electrode are continuously prepared, and the manufacturing of the perovskite solar cell is completed. The preparation method is simple and convenient in steps, raw materials are easy to obtain, the coverage rate and the crystallization quality of the perovskite light absorption layer are effectively improved by improving wettability, interface non-radiative recombination is reduced, the yield and the photoelectric conversion efficiency of the solar cell are remarkably improved, and the solar cell is suitable for large-scale production. The method is suitable for preparation and commercial popularization of high-performance perovskite solar cells.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a perovskite solar cell preparation technology, and specifically discloses a method for improving the wettability of a precursor solution and preparing a high-efficiency solar cell. Background Art

[0002] Solar cells can reduce greenhouse gas emissions and dependence on fossil fuels, and play an important role in achieving the "dual carbon" goal and building an ecological civilization. Metal halide perovskites have become highly competitive thin-film photovoltaic materials with the potential to achieve lower photovoltaic power generation costs due to their excellent optoelectronic properties and low-cost preparation advantages. The use of organic hole transport layers (HTLs) reduces the recombination losses in perovskite solar cells, enabling inverted devices to achieve high performance.

[0003] However, due to the strong hydrophobicity of the carrier transport layer, the perovskite solution cannot fully infiltrate the layer, making it difficult to obtain a dense and smooth perovskite film. The inappropriate interface contact between the hydrophobic transport layer and the perovskite absorption layer leads to a large number of holes in the prepared perovskite film, affecting the performance and yield of solar devices. The perovskite precursor has poor wettability, which leads to uneven distribution of the perovskite film and the formation of gaps at the interface between the perovskite layer and the buried bottom, resulting in a perovskite film with pinholes, which affects the efficiency of perovskite solar cells. Summary of the invention

[0004] In order to overcome the shortcomings of the prior art, the present invention provides a method for improving the wettability of a precursor solution and preparing a high-efficiency solar cell, a method for improving the wettability of a perovskite precursor solution, a nano-metal particle layer is coated on a carrier transport layer by a wet coating process, the wettability of the perovskite precursor is improved, and the coverage of the perovskite light absorbing layer is increased.

[0005] A first aspect of the present invention provides a method for improving the wettability of a precursor solution to prepare a metal oxide layer on a hole transport layer.

[0006] The specific steps are: dissolving the nano metal oxide in anhydrous ethanol or isopropanol to obtain a nano metal oxide precursor solution, and then spin coating the nano metal oxide layer precursor solution on the surface of the hole transport layer to obtain the nano metal oxide layer.

[0007] The nano metal oxide is one of yttrium oxide, aluminum oxide and silicon oxide.

[0008] The nano-metal oxide is dissolved in anhydrous ethanol or isopropanol, and a nano-metal oxide precursor solution is obtained after ultrasonic filtration.

[0009] The ultrasonic time is 20-60 minutes, and a milky white solution is obtained after filtration. Preferably, the ultrasonic time is 30 minutes.

[0010] The concentration of the nano metal oxide precursor solution is 0.01-0.04 wt %. Preferably, the nano metal oxide precursor solution is prepared by dissolving 0.02 wt % of nano yttrium oxide in isopropanol.

[0011] A method for preparing a high-efficiency solar cell comprises the above method for improving the wettability of a precursor solution.

[0012] The method for preparing a high-efficiency solar cell comprises the following steps in sequence:

[0013] (1) preparing a hole transport layer;

[0014] (2) preparing a metal oxide layer on the hole transport layer;

[0015] (3) preparing a perovskite light absorbing layer;

[0016] (4) preparing a passivation layer;

[0017] (5) preparing an electron transport layer and a buffer layer;

[0018] (6) Preparing a metal electrode on the buffer layer to obtain a perovskite solar cell.

[0019] The specific steps include:

[0020] 1) Cleaning the conductive glass; ultrasonically treating the conductive glass in glass cleaning solution and deionized water for 15-30 minutes in turn to remove the impurities attached to the surface of the conductive glass; then ultrasonically treating the conductive glass in ethanol for 10-20 minutes; and finally drying the conductive glass with high-purity nitrogen to obtain the treated conductive glass;

[0021] 2) preparing a hole transport layer; spin coating the conductive glass obtained in step 1) with a hole transport layer precursor solution, and performing a first annealing to obtain a hole transport layer; the hole transport layer is [4-(3,6-dimethoxy-9H-carbazole-9-yl)butyl]phosphonic acid; the precursor solution solvent is anhydrous ethanol or isopropanol; the precursor concentration is preferably 0.5 mg / ml-1.0 mg / ml;

[0022] 3) preparing a nano-metal oxide layer; spin coating a nano-metal oxide precursor on the surface of the hole transport layer to obtain a nano-metal oxide layer;

[0023] 4) preparing a perovskite light-absorbing layer; applying a perovskite precursor solution on the surface of the nano-metal oxide layer, and obtaining the perovskite light-absorbing layer after a second annealing; the perovskite precursor solution comprises one of lead iodide, lead chloride, cesium iodide, formamidine hydroiodide, methylamine hydroiodide, and methylamine hydrobromide, and the solvent of the perovskite precursor solution is N,N-dimethylformamide and / or dimethyl sulfoxide;

[0024] 5) preparing a passivation layer; applying a passivation layer precursor on the surface of the perovskite light absorbing layer to obtain a passivation layer;

[0025] The passivation layer precursor solution is EDAI dissolved in a mixed solvent of isopropanol and chlorobenzene, with a concentration of 0.8-1.2 mg / ml; wherein the volume ratio of isopropanol to chlorobenzene is 2:1;

[0026] 6) preparing an electron transport layer and a buffer layer; applying an electron transport layer precursor solution and a buffer layer precursor solution to the passivation layer in sequence, and performing a third annealing to obtain an electron transport layer and a buffer layer as a substrate;

[0027] The precursor solution of the electron transport layer is (6,6)-phenyl carbon 61 butyric acid methyl ester dissolved in chlorobenzene solvent, with a concentration of 18-22 mg / ml; the precursor solution of the buffer layer is bathocuproin dissolved in isopropanol solvent, with a concentration of 0.4-0.6 mg / ml;

[0028] 7) Preparing a metal electrode; placing a substrate in a vacuum chamber, and vapor-depositing a metal electrode with a thickness of 80nm-110nm on the surface of the substrate through a mask plate; the electrode is one of gold, silver, and copper; the thickness is 80nm-110nm, and the metal electrode is prepared by thermal evaporation or electron beam evaporation.

[0029] The first annealing temperature is 90-110°C, and the annealing time is 10-15min;

[0030] The second annealing temperature is 90-110°C, and the annealing time is 30-45min;

[0031] The second annealing temperature is 90-110° C., and the annealing time is 5-10 min.

[0032] The intended effects of the present invention are:

[0033] The process of the present invention improves the hole transport layer by utilizing the hydrophilicity of nano-metal oxides, thereby improving the wettability of the perovskite precursor solution, thereby effectively improving the coverage and crystallization quality of the perovskite light-absorbing layer, and then continuing to prepare the electron transport layer, buffer layer, passivation layer and metal electrode to complete the production of perovskite solar cells. This preparation method is not only simple in steps and easy to obtain raw materials, but also effectively improves the coverage and crystallization quality of the perovskite light-absorbing layer by improving wettability, while reducing interface non-radiative recombination, significantly improving the yield rate and photoelectric conversion efficiency of solar cells, and is suitable for the preparation and commercial promotion of high-performance perovskite solar cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a structural diagram of a device prepared in Example 1 of the present invention;

[0035] Figure 2 The JV curve diagram of the comparative experiment between Example 1 and Comparative Example 1. Specific implementation plan

[0036] The present invention provides a method for improving the wettability of a perovskite precursor solution and a method for preparing a corresponding solar cell. To make the purpose, technical solution and advantages of the present invention clearer, the present invention is described in detail below. To make the technical problems, technical solutions and beneficial effects to be solved by the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0037] Step 1: Clean the conductive glass (usually FTO or ITO). First, ultrasonicate it in glass cleaning liquid and deionized water for 20 minutes in turn to remove the debris attached to the surface of the conductive glass; then ultrasonicate it in ethanol for 15 minutes for subsequent treatment; finally, blow dry it with high-purity nitrogen to obtain the treated conductive glass.

[0038] Step 2: Prepare the hole transport layer. Prepare a hole transport layer precursor solution of 0.5 mg / ml [4-(3,6-dimethoxy-9H-carbazole-9-yl)butyl]phosphonic acid dissolved in anhydrous ethanol. Place the above conductive glass in a coating machine, spin-coat the hole transport layer precursor solution, and anneal at 100°C for 10 minutes to obtain a hole transport layer.

[0039] Step 3: Prepare a nano-metal oxide particle layer. Prepare a solution of 0.02 wt% nano-yttrium oxide dissolved in isopropanol, and obtain a precursor solution after ultrasonic filtration. Spin-coat the nano-metal oxide layer precursor solution on the surface of the hole transport layer to obtain a nano-metal oxide layer.

[0040] Step 4: Prepare the perovskite light-absorbing layer. Prepare a perovskite precursor solution containing lead iodide, lead chloride, cesium iodide, formamidine hydroiodide, methylamine hydroiodide, methylamine hydrobromide, N,N-dimethylformamide and dimethyl sulfoxide. The content or concentration of each component is 1.5M (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3, dissolved in a mixed solution of DMF:DMSO=4:1 (V / V).

[0041] A perovskite light-absorbing layer is prepared on the surface of the nano-metal oxide layer, a perovskite precursor solution is coated on the surface of the nano-metal oxide layer, and the perovskite light-absorbing layer is obtained after annealing at 100° C. for 45 minutes.

[0042] Step 5: Prepare a passivation layer. Prepare a passivation layer on the surface of the perovskite light absorbing layer, and apply a perovskite precursor solution on the surface of the perovskite light absorbing layer to obtain a passivation layer. The passivation layer precursor solution is EDAI dissolved in a mixed solvent of isopropanol and chlorobenzene, with a concentration of 1 mg / ml; wherein the volume ratio of isopropanol to chlorobenzene is 2:1.

[0043] Step 6: Prepare the electron transport layer and the buffer layer. Prepare (6,6)-phenylcarbon 61 butyric acid methyl ester with a concentration of 20 mg / ml dissolved in chlorobenzene solvent as the electron transport layer precursor solution; prepare bathocuproin with a concentration of 0.5 mg / ml dissolved in isopropanol solvent as the buffer layer precursor solution. The electron transport layer precursor solution and the buffer layer precursor solution are sequentially coated on the surface of the passivation layer, and after annealing at 100°C for 10 minutes, the electron transport layer and the buffer layer are obtained.

[0044] Step 7: Prepare metal electrodes. The prepared substrate is placed in a vacuum chamber, and a metal silver electrode with a thickness of 100 nm is obtained by evaporation through a mask on the surface of the substrate.

[0045] In order to verify that the process of the embodiment of the present invention can significantly improve the preparation of single-junction perovskite solar cells, the present invention provides Example 1 and Comparative Example 1 for demonstration.

[0046] Example 1: Device structure Please refer to the attached drawings of the specification Figure 1 This embodiment provides a single-junction perovskite solar cell 1, which includes, from bottom to top, a conductive glass, a hole transport layer, a nano-metal oxide particle layer, a perovskite light absorption layer, a passivation layer, an electron transport layer, a buffer layer, and a metal electrode. The specific preparation is as described above.

[0047] Comparative Example 1: This comparative example provides a single-junction perovskite battery without a nano-metal oxide layer structure, and the battery structure includes conductive glass, hole transport layer, perovskite light absorption layer, passivation layer, electron transport layer, buffer layer, and metal electrode from bottom to top. The difference from Example 1 is that the third step is omitted in this comparative example.

[0048] A comparative experiment was conducted between Example 1 of the present invention and Comparative Example 1. A standard sunlight intensity calibration was performed using a sunlight simulator. 2 The comparative device was subjected to a long-term JV test, with the starting voltage set to -0.20V, the cut-off voltage set to 1.25V, and the range set to 0.1A. The test results are shown in Table 1. Figure 2 shown.

[0049] Table 1

[0050]

[0051] From the comparison of the above table, we can see that:

[0052] From the comparison between Example 1 and Comparative Example 1, it can be seen that if the nano-metal oxide layer is not used to improve the surface of the hole transport layer, the wet film of the perovskite light absorbing layer cannot evenly cover the surface of the transport layer during preparation, there are many holes, a dense light absorbing layer cannot be formed, and the battery has too many defects.

[0053] In comparison, Example 1 of the present invention has higher open circuit voltage and photoelectric conversion efficiency.

[0054] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for improving the wettability of a precursor solution, characterized in that: A metal oxide layer is formed on the hole transport layer.

2. A method for improving the wettability of a precursor solution according to claim 1, characterized in that: The specific steps are: dissolving the nano metal oxide in anhydrous ethanol or isopropanol to obtain a nano metal oxide precursor solution, and then spin coating the nano metal oxide layer precursor solution on the surface of the hole transport layer to obtain the nano metal oxide layer.

3. A method for improving the wettability of a precursor solution according to claim 2, characterized in that: The nano metal oxide is one of yttrium oxide, aluminum oxide and silicon oxide.

4. The method for improving the wettability of a precursor solution according to claim 2, characterized in that: The nano-metal oxide is dissolved in anhydrous ethanol or isopropanol, and a nano-metal oxide precursor solution is obtained after ultrasonic filtration.

5. The method for improving the wettability of a precursor solution according to claim 4, characterized in that: The ultrasonic time is 20-60 minutes, and a milky white solution is obtained after filtration.

6. The method for improving the wettability of a precursor solution according to claim 4, characterized in that: The concentration of the nano metal oxide precursor solution is set at 0.01-0.04wt%.

7. A method for preparing a high-efficiency solar cell, characterized in that: The method comprising claim 1.

8. A method for preparing a high-efficiency solar cell according to claim 7, characterized in that: The following steps are included in sequence: (1) preparing a hole transport layer; (2) preparing a metal oxide layer on the hole transport layer; (3) preparing a perovskite light absorbing layer; (4) preparing a passivation layer; (5) preparing an electron transport layer and a buffer layer; (6) Preparing a metal electrode on the buffer layer to obtain a perovskite solar cell.

9. A method for preparing a high-efficiency solar cell according to claim 8, characterized in that: The specific steps include: 1) Cleaning the conductive glass; ultrasonically treating the conductive glass in glass cleaning solution and deionized water for 15-30 minutes in turn to remove the impurities attached to the surface of the conductive glass; then ultrasonically treating the conductive glass in ethanol for 10-20 minutes; and finally drying the conductive glass with high-purity nitrogen to obtain the treated conductive glass; 2) preparing a hole transport layer; spin coating the conductive glass obtained in step 1) with a hole transport layer precursor solution, and performing a first annealing to obtain a hole transport layer; The hole transport layer is [4-(3,6-dimethoxy-9H-carbazole-9-yl)butyl]phosphonic acid; the precursor solution solvent is anhydrous ethanol or isopropanol; 3) preparing a nano-metal oxide layer; spin coating a nano-metal oxide precursor on the surface of the hole transport layer to obtain a nano-metal oxide layer; 4) preparing a perovskite light absorbing layer; A perovskite precursor solution is coated on the surface of the nano-metal oxide layer, and after a second annealing, a perovskite light-absorbing layer is obtained; the perovskite precursor solution comprises one of lead iodide, lead chloride, cesium iodide, formamidine hydroiodide, methylamine hydroiodide, and methylamine hydrobromide, and the solvent of the perovskite precursor solution is N,N-dimethylformamide and / or dimethyl sulfoxide; 5) preparing a passivation layer; applying a passivation layer precursor on the surface of the perovskite light absorbing layer to obtain a passivation layer; The passivation layer precursor solution is EDAI dissolved in a mixed solvent of isopropanol and chlorobenzene, with a concentration of 0.8-1.2 mg / ml; wherein the volume ratio of isopropanol to chlorobenzene is 2:1; 6) preparing an electron transport layer and a buffer layer; applying an electron transport layer precursor solution and a buffer layer precursor solution to the passivation layer in sequence, and performing a third annealing to obtain an electron transport layer and a buffer layer as a substrate; The precursor solution of the electron transport layer is (6,6)-phenyl carbon 61 butyric acid methyl ester dissolved in chlorobenzene solvent, with a concentration of 18-22 mg / ml; the precursor solution of the buffer layer is bathocuproin dissolved in isopropanol solvent, with a concentration of 0.4-0.6 mg / ml; 7) Preparing a metal electrode; placing a substrate in a vacuum chamber, and vapor-depositing a metal electrode with a thickness of 80nm-110nm on the surface of the substrate through a mask plate; the electrode is one of gold, silver, and copper; the thickness is 80nm-110nm, and the metal electrode is prepared by thermal evaporation or electron beam evaporation.

10. The method for improving the wettability of a precursor solution according to claim 9, characterized in that: The first annealing temperature is 90-110°C, and the annealing time is 10-15min; The second annealing temperature is 90-110°C, and the annealing time is 30-45min; The second annealing temperature is 90-110° C., and the annealing time is 5-10 min.